2014
DOI: 10.1017/s0007114514001676
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle patterns and dysglycaemic risk in urban Sri Lankan women

Abstract: Specific dietary patterns are associated with the risk of chronic disease. An in-depth understanding more reflective of lifestyle would be possible when assessing the synergistic effects of both diet and physical activity in pattern analysis. In the present study, we examined the biochemical markers of dysglycaemia and cardiometabolic risk in relation to lifestyle patterns using principal component analysis (PCA). Urban women (n 2800) aged 30 -45 years were screened for dysglycaemia using cluster sampling from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
2
5
0
Order By: Relevance
“…Using data stemming from the National STEPwise survey conducted in Qatar in year 2012, we identified three lifestyle patterns amongst Qatari women of reproductive age, with only the “Fast food & smoking” and “Traditional sedentary” patterns being associated with increased risk of raised BP. Together, the identified patterns explained 33.7% of the variance, which falls within the range reported in the literature (23.5%–45%) [ 18 , 20 , 29 ]. Only a few studies have adopted the lifestyle pattern approach and aimed at investigating the combined effects of food intake and other health-related lifestyle characteristics on disease risk [ 18 , 20 , 29 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Using data stemming from the National STEPwise survey conducted in Qatar in year 2012, we identified three lifestyle patterns amongst Qatari women of reproductive age, with only the “Fast food & smoking” and “Traditional sedentary” patterns being associated with increased risk of raised BP. Together, the identified patterns explained 33.7% of the variance, which falls within the range reported in the literature (23.5%–45%) [ 18 , 20 , 29 ]. Only a few studies have adopted the lifestyle pattern approach and aimed at investigating the combined effects of food intake and other health-related lifestyle characteristics on disease risk [ 18 , 20 , 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…Together, the identified patterns explained 33.7% of the variance, which falls within the range reported in the literature (23.5%–45%) [ 18 , 20 , 29 ]. Only a few studies have adopted the lifestyle pattern approach and aimed at investigating the combined effects of food intake and other health-related lifestyle characteristics on disease risk [ 18 , 20 , 29 ]. A brief description of these studies is presented in the table below ( Table 5 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Previous studies examining the effect of combined lifestyle factors on other metabolic abnormalities showed similar results. A lifestyle pattern consisting of a higher snack and dairy consumption and lower levels of physical activity was associated with obesity and unfavorable glycaemic indices, lipid profile and increased high-sensitivity C-reactive protein concentrations among urban Sri Lankan women [ 4 ]. In addition, a previous study by our group investigating the role of combined lifestyle factors on elevated blood pressure showed that a higher adherence to the ‘Fast food and smoking’ and the ‘Traditional and sedentary’ patterns increased its odds among Qatari women [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when a large number of variables are entered in a regression model, it is possible to obtain significant association simply by chance [ 3 ]. Recently, a novel approach in nutritional epidemiology has been proposed whereby lifestyle patterns, as a combination of diet, physical activity and smoking are examined in relation to diseases such as diabetes [ 4 ]; obesity [ 5 ] and hypertension [ 1 , 6 ]. Not only does this approach account for the collinearity between risk factors, it also captures the complexity of real lifestyle effect on disease risk and leads to a better understanding of high-risk behaviors.…”
Section: Introductionmentioning
confidence: 99%